Prevalence of hemophilia in six cuban provinces - Castillo-González, Dunia; Lardoeyt-Ferrer, Roberto; Almagro-Vázquez, Delfina; Lam-Díaz, Rosa M; Lavaut-Sánchez, Kalia; Gutierrez-Díaz, Adys; Campo-Díaz, Mirtha; Alvarez-Vega, Nereyda; Salinas-González, Jorge Luis; Fernández-Aguila, Julio; Agramonte-Llanes, Olga (Revista Cubana de Hematología, Inmunología y Hemoterapia, 2013)
Introduction: Hemophilia is an inherited bleeding disorder; its incidence is almost constant in different populations. Since the 80th decade a multidisciplinary group for the care of patients with hemophilia was created at the Instituto de Hematología e Inmunología. Nowadays a national comprehensive care program allows patients to receive a continuous monitoring and an effective treatment. Objective: To know prevalence of patients with hemophilia in Cuba. Results: Data of 229 patients from 5 provinces and the special municipality Isla de la Juventud were included, which covered 58,71% of the total patients registered in Cuba. The information included demographic data, severity of hemophilia, presence of inhibitors and infection status for viral diseases. Hemophilia A patients were 188 (82.10 %) and 41 (17.90 %) with hemophilia B. The disease was severe in 56.33 % of patients, moderate in 24 %, and mild in 19.70 %. Inhibitors were present in 17.03 % of the patients. Human immunodeficiency virus infection was present only in 0.87 % of patients and hepatitis C virus infection in 39.03 %. The mean age at diagnosis was 2.15 years. Conclusions: The general age-adjusted prevalence was 9.63 cases of hemophilia per 100 000 male and the main prevalence of patients was found in ages between 20 and 59 years.